EFFECTIVENESS OF BACK EFFLUERAGE MASSAGE THERAPY USING CLOVE OIL ON UNDER BACK PAIN IN POSTPARTUM MOTHER - Rini Rahmayanti; Yola Yolanda (Nurse and Health: Jurnal Keperawatan, 2019)
Background: Low back pain is one of the complaints felt by most or even almost all postpartum mothers since pregnancy. The prevalence of events ranges from 20-90% since pregnancy. About 80% of postpartum mothers experience low back pain after a normal delivery. One type of complementary therapy that can be done to increase the pain threshold is back effluerage massage with clove oil. Cloves contain components of eugenol compounds that have analgesic effects.Objectives: The purpose of this study was to determine the effectiveness of back effluerage massage therapy using clove oil on lower back pain in postpartum mothers.Methods: This study uses a Quasi-Experiment method with the design of One Group Pretest-Posttest. The sample in this study was postpartum mothers with vaginal delivery who experienced lower back pain. Consecutive sampling technique will be used to determine the sample. The number of samples taken in this study were 20 people as a treatment group. The instrument used was an observation sheet to determine the pain scale of the respondent. This research will be carried out within one year. The results of the study will be analyzed by paired T test.Results: The results obtained p value 0.005 (p value <0.05) so that there is an effect of back effluerage massage therapy using clove oil on lower back pain in postpartum mothers.Conclusion: The results of this study are expected to evaluate the effect of back effluerage massage therapy using clove oil on lower back pain in postpartum mothers. Key words: Back Effluerage Massage, Clove Oil, Low Back Pain, Postpartum Mothers.